Forced expression of PDX-1 gene makes hepatoma cells to acquire glucose-responsive insulin secretion while maintaining hepatic characteristic - Hashimoto, H; Higuchi, Y; Kawai, K (Cellular and Molecular Biology, 2015)
Evidence shows that forced expression of the PDX1 gene converts hepatoma cells, mouse liver epithelial cells (MLECs) and HepaRG cells, into insulin-producing cells, Î²-cells, or islets of Langerhans. However, no reports have investigated the characteristics of mouse or human hepatocytes introduced with the PDX1 gene over prolonged observation periods. In this study, we immunohistologically and molecularly investigated the alternative processes induced by PDX1 gene introduction in mouse and human hepatocytes over prolonged observation periods using immunocytochemistry, immunofluorescence, polymerase chain reaction (PCR), Western blotting, and flow cytometry (FCM) analysis. Immunocytochemical and immunofluorescent observations showed that MLECs and HepaRG cells on 2 and 21 days after introduction of the PDX1 gene comprised cells double-positive for insulin and albumin. Additionally, they showed MAFA expression and glucose-responsive insulin secretion with glucokinase expression. However mouse embryonic fibroblasts introduced with PDX1-GFP could not acquire glucose-responsive insulin secretion and glucokinase expression. Subsequently, we hypothesized that the number of albumin-positive MLECs and HepaRG cells would decrease after introduction of PDX1 due to the conversion of MLECs and HepaRG cells into insulin-producing cells. However, FCM analysis indicated that the number of albumin-positive MLECs and HepaRG cells was not altered by the introduction of PDX1. We thought that MLECs and HepaRG cells introduced with the PDX1 gene could acquire a functional insulin secretory capacity without conversion to Î²-cells, or islets of Langerhans, and the acquisition could need glucokinase expression.